Correlation between metabolite profile and phytochemical characteristics of Ipomoea aquatica Forssk. with its antioxidant and α-glucosidase inhibitory activities using NMR-based metabolomics - Lawal, Umar (2016)
Ipomoea aquatica Forssk. (morning glory) is a green leafy vegetable that is rich in minerals, proteins, vitamins, amino acids and secondary metabolites. The aims of the study were to discriminate Ipomoea extracts by 1H NMR spectroscopy in combination with chemometrics method and to determine their antioxidant and α-glucosidase inhibitory activities. In the first part of the study, different types of I. aquatica cultivar such as the upland type has narrow leaves (K-11), the low-land and aquatic type, have broader, arrow-shaped leaves, (K-25) and bamboo shaped leaves (K-88), extracted using water and methanol at various concentrations were investigate for their effects on the total phenolics, antioxidant and α-glucosidase inhibitory activities. This study indicates that 70% methanol was the most efficient solvent for the extraction of phenolic compounds from I. aquatica cultivars. Thus, for the second part of the study 1H NMR combined with multivariate data analysis was applied for the metabolic profiling of three cultivars of I. aquatica extracted with 70% methanol. The orthogonal partial least squares discriminant analysis (OPLS-DA) indicated a clear separation among cultivars. The relative levels of various compounds such as amino acids, organic acids, sugars and phenolic compounds were specific to each cultivar. Among the three cultivars, the K-11 was the most active for the antioxidant and α-glucosidase inhibitory activities and was selected for the third part of the study. Proton nuclear magnetic resonance (1H NMR) spectroscopy was combined with multivariate data analyses to distinguish the K-11 cultivar at different developmental stages. A principal component analysis (PCA) of I. aquatica provides clusters based on the different developmental stages by combining principal components PC1 and PC2 with a total variance of 65.1%. The initial stages (weeks 3 and 4) showed comparatively low contents of phenolic and organic acids, such as citric and maleic acid; the latter stages (weeks 5 and 6) exhibited higher glucose and phenolic compound contents. The sugar, phenolic compound, fatty and formic acid contents increased based on the developmental stages of the I. aquatica. The latent structures were projected using a partial least squares (PLS) model to predict the biological activity of the Ipomoea extracts based on their 1H NMR spectra. The results showed that six-week-old plants were the most active, showing an accumulation of epicatechin, protocatechuic acid, rutin and maleic acid. In addition, three compounds namely 3,5-di-O-caffeoylquinic acid (83) and 4,5-di-O-caffeoylquinic acid (84) and quercetin-3-O-β-glucoside (85) were isolated from six-week-old of the K-11 cultivar. The structures of these compounds were elucidated using various spectroscopic techniques including UV, ESIMS, 1D- and 2D-NMR. Compounds (83) and (84) exhibited good antioxidant activity with IC50 values of 4.85±0.06 μg/mL and 6.65±0.12 μg/mL, respectively, and compound (85) exhibited the lowest activity with IC50 values of 7.66±0.19 μg/mL compared to standard BHT; 6.25±0.15 μg/mL. A similar trend was observed for α- glucosidase inhibitory activity. In conclusion, this study may serve as a starting point for further research on phytochemicals from I. aquatica and can aid in the development of medicinal preparation, nutraceutical and functional food.